An Expert Systems Approach to the Socio-economic Evaluation of Rural Land-use Policy - Sharma, R. A.; Skerratt, S. (Indian Forester, 1995)
Rural policy makers are only now recognising the importance of incorporating socio-economic data into policy analysis in order to increase policy impact and uptake. This paper uses two specific case studies; the impact and uptake of social forestry policy in Orissa (India) and of Environmentally Sensitive Area Policy in Breadalbane (UK), to highlight the need and opportunities for incorporating qualitative Socio-economic data into policy analysis. The role of expert systems as a means of synthesising both qualitative and quantitative data is discussed and illustrated. Expert systems are found to have a potential role in the socio-economic evaluation of land-use policy but they are not seen as a replacement for analytical techniques, such as social cost benefit analysis, but rather as a means of enhancing the analysis in order to provide for better decision making.